Pulmonary Arterial Hypertension Specific Therapy in Patients with Combined Post- and Precapillary Pulmonary Hypertension. (1st March 2018) - Alfraidi, Hassan; Qanash, Sultan; Bshouty, Zoheir
Abstract : Background . Specific therapy for patients with PAH is associated with good outcomes. Little is known about the effect of this treatment in patients with Cpc-PH (PAPm ≥ 25 mmHg, PAWP > 15 mmHg, DPG ≥ 7 mmHg, and/or PVR > 3 WU). This study evaluates the outcome of treating patients with Cpc-PH using PAH specific therapy. Methods . The primary outcome was survival. Secondary outcomes were WHO functional class and 6-minute walk distance (6-MWD). Results . Twenty-six patients with Cpc-PH (half with VHD and half with HF) received PAHST. Six patients did not tolerate treatment due to pulmonary edema. No predictors for treatment intolerance were identified. In twenty patients who tolerated the treatment, the mean WHO functional class improved from2.70 ± 0.21 at initial assessment to2.22 ± 0.21 (p < 0.04 ) and2.06 ± 0.21 (p < 0.03 ) at 6 and 9 months, respectively. Mean 6-MWD improved from276.0 ± 38.50 meters at initial assessment to343.9 ± 22.99 meters (p < 0.04 ) and364.6 ± 34.85 meters (p = 0.07 ) at 6 and 9 months, respectively. Twelve patients died during the follow-up period. Mean survival for all patients was1279.7 ± 193.60 days. Conclusion . PAHST may be beneficial in the treatment of Cpc-PH (both short and long term). Prospective randomized controlled trials of PAHST in this population are needed to assess its potential efficacy.